The influence of harvesting free gingival graft on self-reported pain perception: A randomized two-arm parallel clinical trial - Niusha Namadmalian Esfahani; Afshin Khorsand; Seyedhossein Mohseni Salehimonfared (Elsevier, 2021)
Background/purpose: Free gingival graft (FGG) is used as an effective method to increase the width of keratinized tissue. However, it can cause pain at the donor site. Techniques accompanied by lesser tissue harvesting can reduce pain after surgery. The purpose of this study was to evaluate the self-reported pain perception following harvesting FGG using conventional and accordion methods. Materials and methods: In this randomized clinical trial study, 31 patients with a deficiency of keratinized tissue around implant were investigated. Sixteen subjects in the accordion group and 15 subjects in the control group received conventional FGG. In the accordion group, FGG was harvested with a length of 60% of the mesiodistal length of the recipient area and with the same length as the mesiodistal length of the recipient area in the conventional group. The patients were asked to record their daily pain using a numerical rating scale. Results: The severity of the pain after reaching to the peak on the second day was reduced and reached zero at day 14 in both groups. Pain severity showed no significant difference between the treatment groups. The highest level of pain was reported in the conventional group in those subjects under 50 years old, and the lowest one was in the conventional group's subjects above 50 years old. There was no difference between men and women in the reported pain between the treatment groups. Conclusion: Harvesting graft with a smaller size in the accordion group has no effect on reducing pain. Registration number: IRCT20190721044296N1.